The importance of grazing regime in the provision of breeding habitat for grassland birds: The case of the endangered little bustard (Tetrax tetrax) - Faria, Nuno; Rabaça, João E.; Morales, Manuel B. (Journal for Nature Conservation, 2012)
In Mediterranean dry grasslands, grazing by domestic animals is an important agricultural activity on dry grasslands. Several bird species occur in these grazed habitats and are now experiencing a near continuous decline. We investigated the impact of livestock grazing on the threatened little bustard (Tetrax tetrax L.). The study was conducted at the NATURA 2000 Site/Important Bird Area of Cabrela, Portugal. Our main goals were to investigate responses of little bustard territorial males and breeding females to different livestock management practices, namely pasture types, stocking rates and sward structure. Bird distribution was surveyed using car and foot surveys. Data on grazing was supplied by land managers every 10 days from February to June through ﬁeld interviews. Generalised additive models and model averaging were used to compute predictive models. Results indicate that higher probabilities of occurrence were found in long-term pastures and under light-moderate grazing conditions (stocking rates around 0.4 LU/ha). Conversely, lower probabilities of occurrence were found in ungrazed or heavy grazed ﬁelds. Males occurred mostly in large ﬁelds, but this variable seemed to be less important for females. On the other hand, green plant cover and the vegetation height were good predictors for the occurrence of females but not for males. Females used mostly pastures with vegetation height around 20–25 cm. Our results suggest that grazing management plans that aim to conserve little bustard populations should consider (1) the maintenance of the larger long-term pastures and (2) the use of light-moderate stocking rates (0.2–0.6 LU/ha).
Keywords: Green plants; livestock; pasture management; Stocking rates; Tetrax tetrax; vegetation structure

Linking plant composition and arthropod abundance to establish little bustard breeding requirements in pastureland dominated landscapes - Faria, Nuno; Rabaça, João E.; Morales, Manuel B. (Biodiversity and Conservation, 2012)
Most research on steppe bird habitat selection has been focused on the effects of management regimes or vegetation structure. However, much less is known on how plant composition is related with steppe bird occurrence. We investigated microhabitat of little bustard territorial males and females during the nesting and chick-rearing season in areas with dominance of pastureland focusing on plant composition. We searched for relationships between preferred vegetation and arthropod abundance in order to identify the contribution of different vegetation typologies in providing essential trophic resources for the species. Surveys of little bustards were made using car and foot transects. Plant composition was obtained within a 50 9 50 cm square at four sampling replicates and arthropod availability was sampled using a sweep net. Statistical procedures were conducted in three steps: (1) analysis of variance was used to identify at univariate level the plant composition and arthropod variables that were signiﬁcantly related with both male and female occurrence sites; (2) principal components analysis was performed using the variables with signiﬁcant results at univariate level; (3) model averaging on generalized linear and mixed models was applied to evaluate the selection probability of each principal component. The species occurs in sites with high ﬂoristic richness and high abundance of Fabaceae species, although plant composition differs from male to female sites. These variables were found to be crucial to provide higher abundances of arthropods, notably of Acrididea, Formicidae and some groups of Coleoptera which are decisive for the selection of displaying or female breeding sites.
Keywords: Acrididae; Fabaceae; grassland; Microhabitat selection; Plant richness; Tetrax tetrax